Case Report: Double-Decker Repair of Partial Pulmonary Venous Return Into the Coronary Sinus - Jiang, Xuan; Liu, Jinduo; Liu, Yueheng; Gu, Tianxiang (Frontiers in Cardiovascular Medicine, 2022)
We present a case of persistent left superior vena cava(LSVC) draining into the right atrium(RA) via the coronary sinus(CS), while the left superior pulmonary vein returns abnormally to the CS. The LSVC may have few clinical consequences but complicates surgical repair of partial anomalous pulmonary venous return(PAPVR). Transthoracic echocardiography and computed tomographic angiography(CTA) showed that a persistent LSVC and PAPVR converged behind the left atrium. During the operation, the left atrium was adjacent to the confluence part. We resected a portion of the adjacent left atrium to create an inlet of the pulmonary veins and used two autologous pericardial patches to reconstruct a tunnel directing flow from the left pulmonary veins to the surgically created inlet in the adjacent left atrium, and another upper tunnel directing flow from the LSVC to the dilated CS. Pulmonary CTA confirmed that both PAPVR flow to LA and LSVC flow to RA were unobstructed. At a 12-month follow-up, the patient was asymptomatic. No supraventricular arrhythmia was detected. We would like to present this additional technique to our armamentarium to treat PAPVR in combination with LSVC.